УМУМТАЪЛИМ МАКТАБЛАРИДА БОШЛАНҒИШ СИНФ ЎҚУВЧИЛАРИНИНГ ПСИХОЛОГИК ХУСУСИЯТЛАРИ - Қурбамуратова, З. (SCIENCE and SOCIETY, 2016)
The article deals with the psychological characteristics of younger students and their individual development. One of the features of this age stage is the presence of specific needs. Revealing the essence of these requirements and, at the same time, the acquisition of knowledge, skills and perception of reality by students is the purpose of writing this article.